The Problem-Oriented Record - Muñóz Tapia, Julio (1998)
The advancement of medicine is carried out according to two different processes: the first deals with the quantitative and qualitative accumulation of knowledge, the second concerns the methodology of the application of these medical knowledge. In this regard, the current era is characterized by the synthesis of Technology to "overspecialization" which has undoubtedly led to the advancement of health science, but on the other hand has led to fragmentation of Medicine, with consequent "tunnel vision" and cold application of auxiliary tests against the latest generation sick.